A Study to Assess the Effect of Structured Teaching Program on Knowledge Level Regarding Legal and Ethical Aspects among Staff Nurses Working at Selected Hospital, Lucknow - Khanal, Pratiksha (Crimson Journal of Science and Technology, 2025)
Introduction: This study aims to evaluate the effectiveness of a structured teaching program in enhancing staff nurses' knowledge of legal and ethical issues in selected hospitals. With an increasing emphasis on legal and ethical responsibilities in healthcare, empowering nurses with adequate knowledge in these areas is essential for high-quality patient care and professional accountability.Methods: A pre-experimental, one-group pre-test and post-test design was employed, involving 30 staff nurses from selected hospitals. Participants' knowledge levels were assessed before and after the structured teaching program. Data were collected through a knowledge assessment tool focusing on legal and ethical aspects relevant to nursing.Results: The findings demonstrated a substantial improvement in participants' knowledge post-intervention. Initially, 86.7% of nurses had moderate knowledge, and 13.3% showed inadequate knowledge. After the program, 66.7% achieved adequate knowledge, and 33.3% retained moderate knowledge. This shift indicates that the structured teaching program significantly enhanced the nurses' understanding of legal and ethical aspects.Conclusions: The structured teaching program proved effective in improving staff nurses' knowledge of legal and ethical responsibilities in healthcare settings. Such educational initiatives are crucial for reinforcing nurses' preparedness in handling legal and ethical challenges, ultimately contributing to better patient outcomes and professional practice.